Free‐breathing variable flip angle balanced SSFP cardiac cine imaging with reduced SAR at 3T. Issue 4 (28th October 2015) - Srinivasan, Subashini; Kroeker, Randall M.; Gabriel, Simon; Plotnik, Adam; Godinez, Sergio R.; Hu, Peng; Halnon, Nancy; Finn, J. Paul; Ennis, Daniel B.
Abstract : Purpose: To develop a free‐breathing variable flip angle (VFA) balanced steady‐state free precession (bSSFP) cardiac cine imaging technique with reduced specific absorption rate (SAR) at 3 Tesla. Methods: Free‐breathing VFA (FB‐VFA) images in the short‐axis and four‐chamber views were acquired using an optimal VFA scheme, then compared with conventional breath‐hold constant flip angle (BH‐CFA) acquisitions. Two cardiac MRI experts used a 5‐point scale to score images from healthy subjects (N = 10). The left ventricular ejection fraction, end diastolic volume (LVEDV), end systolic volume, stroke volume (LVSV), and end diastolic myocardial mass (LVEDM) were determined by manual contour analysis for BH‐CFA and FB‐VFA. A pilot evaluation of FB‐VFA was performed in one patient with Duchenne muscular dystrophy. Results: FB‐VFA SAR was 25% lower than BH‐CFA with similar blood–myocardium contrast. The qualitative FB‐VFA score was lower than the BH‐CFA for the short‐axis (3.1 ± 0.5 versus 4.3 ± 0.8; P < 0.05) and the four‐chamber view (3.4 ± 0.4 versus 4.6 ± 0.6; P < 0.05). The LVEDV and the LVSV were 5% and 12% larger ( P < 0.05) for FB‐VFA compared with BH‐CFA. There was no difference in LVEDM. Conclusion: FB‐VFA bSSFP cardiac cine imaging decreased the SAR at 3T with image quality sufficient to perform cardiac functional analysis. Magn Reson Med 76:1210–1216, 2016. © 2015 Wiley Periodicals, Inc.